(untitled) (Progressive Agriculture, 2013)
This study was conducted to estimate the comparative profitability of Aftab Bahumukhi Farm Limited (ABFL) supervised broiler farms and farmers own managed broiler farms. Data were collected from randomly selected 90 broiler farmers of which 45 were ABFL supervised farmers and 45 were own managed farmers. Descriptive statistical techniques were used to estimate cost and returns of broiler farming. The study revealed that on an average, total cost of raising broiler per batch per 1000 birds was estimated at Tk. 99,429.00 and Tk. 1,06,330.00 for ABFL supervised farms and farmers own managed farms respectively. The respective average variable costs and fixed costs per batch per 1000 birds were calculated at Tk. 96,218.00 and Tk. 1,02,926.00 respectively. These accounted for 96.77 percent and 96.80 percent of total costs respectably for ABFL supervised farms and independently managed farms. The estimated average gross return was Tk. 1,03,334.00 for ABFL supervised farms and Tk. 1,09,961.00 for independent farms respectively. The average gross margins per batch per farm for 1000 birds were at Tk. 7,470.00 and Tk. 7,035.00 for the ABFL supervised farms and for farmers own managed farms respectively and average net returns were estimated at Tk. 4,259.00 for ABFL supervised farms and Tk. 3,631.00 for farmers own managed farms respectively. From the statistical evidence it was found that profit earned by ABFL supervised broiler farms and own managed broiler farms were not significantly different. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16875 Progress. Agric. 20(1 & 2): 231 236, 2009